2017
DOI: 10.3389/fimmu.2017.00047
|View full text |Cite
|
Sign up to set email alerts
|

CpG-ODN Shapes Alum Adjuvant Activity Signaling via MyD88 and IL-10

Abstract: Aluminum-containing adjuvants usually referred as Alum are considered as T helper type-2 (Th2) adjuvants, while agonists of toll-like receptors (TLRs) are viewed as adjuvants that favor Th1/Th17 immunity. Alum has been used in numerous vaccine formulations; however, its undesired pro-Th2 adjuvant activity constitutes a caveat for Alum-based vaccines. Combining Alum with TLR-dependent, pro-Th1/Th17 adjuvants might dampen the pro-Th2 activity and improve the effectiveness of vaccine formulations. Here, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
2
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 38 publications
(53 reference statements)
9
50
2
14
Order By: Relevance
“…Since in WT B6 mice, the sensitization with B. tropicalis extract+CpG/Alum does not result in any overt type of airway inflammation and it blocked B. tropicalis ‐specific anaphylactic Abs, we concluded that this type of sensitization prevents the alum's Th2 promoting activities and induces an a nonpolarized cellular immunity. These findings reinforce our previous studies indicating that TLR agonists could be potentially used in formulations of vaccines against allergy . However, it should be noted that depending on the allergen and the TLRs agonists used, different outcomes might occur.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Since in WT B6 mice, the sensitization with B. tropicalis extract+CpG/Alum does not result in any overt type of airway inflammation and it blocked B. tropicalis ‐specific anaphylactic Abs, we concluded that this type of sensitization prevents the alum's Th2 promoting activities and induces an a nonpolarized cellular immunity. These findings reinforce our previous studies indicating that TLR agonists could be potentially used in formulations of vaccines against allergy . However, it should be noted that depending on the allergen and the TLRs agonists used, different outcomes might occur.…”
Section: Discussionsupporting
confidence: 91%
“…We have previously shown using the OVA‐asthma model that IL‐10‐deficient mice developed an intense Th1‐like airway inflammation . Therefore, we tested our protocols of B. tropicalis sensitizations and challenge in IL‐10 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations